miR-221 suppresses ICAM-1 translation and regulates interferon-γ-induced ICAM-1 expression in human cholangiocytes - Hu, Guoku (American Physiological Society, 2010)
Aberrant cholangiocyte reactions in response to inflammatory stimuli are important pathogenic factors for the persistent biliary inflammation in patients with cholangiopathies. Overexpression of intercellular cell adhesion molecule-1 (ICAM-1) in cholangiocytes is a common pathological feature in inflammatory cholangiopathies and can promote cholangiocyte interactions with effector lymphocytes in the portal region. In this study, we tested the involvement of miRNA-mediated posttranscriptional regulation in IFN-γ-induced ICAM-1 expression in cholangiocytes. Using both immortalized and nonimmortalized human cholangiocyte cell lines, we found that IFN-γ activated ICAM-1 transcription and increased ICAM-1 protein expression. Inhibition of ICAM-1 transcription could only partially block IFN-γ-induced ICAM-1 expression at the protein level. In silico target prediction analysis revealed complementarity of miR-221 to the 3′-untranslated region of ICAM-1 mRNA. Targeting of ICAM-1 3′-untranslated region by miR-221 resulted in translational repression in cholangiocytes but not ICAM-1 mRNA degradation. Functional inhibition of miR-221 with anti-miR-221 induced ICAM-1 protein expression. Moreover, IFN-γ stimulation decreased miR-221 expression in cholangiocytes in a signal transducer and activator of transcription 1-dependent manner. Transfection of miR-221 precursor abolished IFN-γ-stimulated ICAM-1 protein expression. In addition, miR-221-mediated expression of ICAM-1 on cholangiocytes showed a significant influence on the adherence of cocultured T cells. These findings indicate that both transcriptional and miRNA-mediated posttranscriptional mechanisms are involved in IFN-γ-induced ICAM-1 expression in human cholangiocytes, suggesting an important role for miRNAs in the regulation of cholangiocyte inflammatory responses.